Antioxidant and anti-inflammatory effect of Asphodelus microcarpus methanolic extracts. (15th July 2019) - Mayouf, Nozha; Charef, Noureddine; Saoudi, Soulef; Baghiani, Abderrahmane; Khennouf, Seddik; Arrar, Lekhmici
Abstract: Ethnopharmacological relevance: Asphodelus microcarpus is an important medicinal plant belonging to family Liliaceae. This plant is used in traditional medicine to treat abscesses by local application of the powder; the roots are used against white spots, and specifically used for ear pain. Aim of the study: The aim of the present study was to assess the in vitro antioxidant effects and the in vivo anti-inflammatory activity of the different parts methanolic extracts of the Asphodelus microcarpus : aerial part (APME), leaf (LME), stem flowers (SFME) and root (RME). Material and methods: The antioxidant potency of extracts was evaluated by DPPH (2, 2-diphenyl-l-picrylhydrazyl), ABTS, β-carotene bleaching assays, iron chelating, free hydroxyl radicals (HO ) assays, and reducing power. The anti-inflammatory effect of the extracts was evaluated using the carrageenan induced rat paw edema and xylene-induced ear edema in mice. Results: The estimation of polyphenols and flavonoids showed that the leave methanolic extract contains a high amount of polyphenols and flavonoids: 755.3 ± 0.036 mg Gallic acid equivalent and 42.2 ± 0.043 mg Rutin equivalent/g of dried material, respectively. Oral administration of the APME and RME extract produced significant (p < 0.05) anti-edematogenic effect with a dose of 500 mg/kg in the carrageenan induced paw edema after 6 h (58.04%, 58.75%, respectively). APME, LME; SFME and RME extracts at 100, 300 and 500 mg/kg, exhibited significant (p < 0.05) inhibition of xylene induced ear edema. Conclusion: the present study confirms the use of A. microcarpus in traditional medicine as anti-inflammatory agent. Graphical abstract: Image 1